John R. Searle: Freedom & Neurobiology. Reflections on Free Will, Language, and Political Power, Nueva York: Columbia University Press, 2007, 113 pp. - Patarroyo, Carlos G. (2007)
Searle goes no further, offers no more arguments or makes deeper in-quiries. Just as what happens with the first chapter of the book, what he offers here is a series of ideas about the possible approaches to a problem, but there is no intention here of providing a definitive answer nor a complete theory. This does not make his book any less attractive; it contextualizes within the general project of the author the two topics here considered, and offers new and modified versions of the published ideas in his other works, which differ even from the versions of this same book in other languages